2021
DOI: 10.1177/22925503211003840
|View full text |Cite
|
Sign up to set email alerts
|

WALANT Hand and Upper Extremity Procedures Performed With Minor Field Sterility Are Associated With Low Infection Rates

Abstract: Background: The use of minor field sterility in hand/upper extremity cases has been shown to improve workflow efficiency while maintaining patient safety. As this finding has been limited to specific procedures, we investigated the safety of performing a wide array of hand/upper extremity procedures outside the main operating room using minimal field sterility with Wide-Awake Local Anaesthesia No Tourniquet (WALANT) anaesthesia by evaluating superficial and deep infection rates across a diverse series of cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Likewise, the need for full prep and drape of the patient versus field sterility is debated, with field sterility being widely used with no increase in the infection rate. 5 , 6 We have used full prep and drape in both cohorts of patients as we did not wish to change too many aspects of care away from our standard practice at once, especially at a time when all other elective work in our hospital has been stopped except cancer work. We needed to demonstrate that this was a safe service that could continue during what was the current wave of the pandemic and in future waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the need for full prep and drape of the patient versus field sterility is debated, with field sterility being widely used with no increase in the infection rate. 5 , 6 We have used full prep and drape in both cohorts of patients as we did not wish to change too many aspects of care away from our standard practice at once, especially at a time when all other elective work in our hospital has been stopped except cancer work. We needed to demonstrate that this was a safe service that could continue during what was the current wave of the pandemic and in future waves.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, this has been known as wide-awake local anesthesia no tourniquet (WALANT) surgery and is routinely performed away from the main theater environment including community settings around the world. 2 - 7 …”
Section: Introductionmentioning
confidence: 99%
“…These impressive results were supported by subsequent studies that involved more complex procedures performed using WALANT, including ORIF of distal radius fractures, repair of spaghetti wrist, and neve reconstructions. 2e5 In a study by Avoricani et al, 20 amongst 265 WALANT cases under field sterility (including 16 distal radius ORIF cases), there was a 0% rate of infections at 14 days after surgery and a 0.37% rate of infection at 30 days after surgery. This 1 case occurred in a delayed flexor tendon repair.…”
Section: Sterilitymentioning
confidence: 99%
“…With this trend, it is important to consider how the procedure room differs from the traditional operating room. First, the use of field sterility instead of main-operating-room sterility has allowed for considerable cost and waste reductions, without impacting upon the likelihood of surgical site infections (Figure 1) [29][30][31]. Instead of needing the full standard set-up for main-operating-room sterility (which includes head covers, neck-to-knee sterile surgeon gowns, shoe covers, laminar airflow, and full-patient-body sterile draping), CTR can safely be performed in a clinic's procedure room with nothing more than a mask, sterile gloves, and single drape.…”
Section: Operative Set-up and Resource Optimizationmentioning
confidence: 99%
“…Thus, it is possible that WALANT could be associated with more surgical site infections. However, no studies to date have demonstrated higher infection rates when WALANT has been used, regardless of operative location, type of sterility used, or composition of personnel present for the procedure [29,30,33,[35][36][37][38][39].…”
Section: Infectionsmentioning
confidence: 99%